2010
DOI: 10.1063/1.3429231
|View full text |Cite
|
Sign up to set email alerts
|

Martensitic transformation and accompanying magnetic changes in Ni–Fe–Ga–Co alloys

Abstract: Two series of cobalt substituted Ni–Fe–Ga ferromagnetic shape memory alloys with lower gallium content (<27 at. %) were studied by differential scanning calorimetry, x-ray diffraction, and thermomagnetic measurements. Co substitution for Fe or Ni promotes an increase in the Curie temperatures and a variation in the martensitic transformation (MT) temperatures, in accord with the alloy valence electron concentration change. For alloys with MTs below room temperature, a field dependent thermomagnetic hyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…For the LG ribbons with a more stable composition, the TT2 promote a slight increase of the Curie temperature as effect of the structure refinement and atomic ordering. In addition, it is observed the largest magnetization drop during the martensitic transformation, reflecting higher magnetocrystalline anisotropy of martensite [19] Surprisingly, but also attesting the accuracy of the magnetic measurements, the thermomagnetic measurements reveal the martensitic transformation even on the ribbons subjected to in situ DSC scans. The very large thermal hysteresis, obtained for VLG and LG samples after DSC scans extended over 100 degrees, may be due to precipitation of secondary phases, compositional inhomogeneities or crystallite size reduction.…”
Section: Magnetometry Datamentioning
confidence: 58%
See 1 more Smart Citation
“…For the LG ribbons with a more stable composition, the TT2 promote a slight increase of the Curie temperature as effect of the structure refinement and atomic ordering. In addition, it is observed the largest magnetization drop during the martensitic transformation, reflecting higher magnetocrystalline anisotropy of martensite [19] Surprisingly, but also attesting the accuracy of the magnetic measurements, the thermomagnetic measurements reveal the martensitic transformation even on the ribbons subjected to in situ DSC scans. The very large thermal hysteresis, obtained for VLG and LG samples after DSC scans extended over 100 degrees, may be due to precipitation of secondary phases, compositional inhomogeneities or crystallite size reduction.…”
Section: Magnetometry Datamentioning
confidence: 58%
“…The calorimetric scans ( Fig.1) reveal that TTs induce, aside from changes of the transformation heat (associated with the DSC peak area), a decrease of the MT temperatures, as more pronounced as the temperature and the duration of the TT increases. The thermograms for the bulk alloys are also included for comparison [19,20]. As a general trend it is observed that for higher Ga content, the MT temperature is less influenced by the thermal treatment.…”
Section: Calorimetry Datamentioning
confidence: 99%
“…In the present study, we examine the superelastic properties and the stress-induced martensite stabilization in a single crystal of NiFeGaCo FSMA with composition which is not prone to showing a second-phase precipitation [29,30]. The stress-strain measurements have been systematically performed on the sample cut along <110> A crystallographic axis of the cubic austenite since the deformation in this direction is crucial for obtaining a giant rubber-like behavior in an SIM-aged conditioned martensitic state [19], or developing a two-way SME [14], or modifying a character of the thermally induced strain recovery in such FSMAs [31].…”
Section: Introductionmentioning
confidence: 99%
“…Thermomagnetic measurements on Ni 55 Fe 20 Ga 25 alloys revealed evidence of two magnetic phases showing different Curie temperatures. [ 104 ] The lower T C (primary) phase was ascribed to the martensitic transition (MT) phase, and the higher T C phase (secondary) corresponded to the γ‐FCC of the alloy. The primary phase showed an order–disorder transition above RT (room temperature).…”
Section: Concerns With the Curie Transition Events In Ferromagnetic A...mentioning
confidence: 99%